2015
DOI: 10.1093/ejcts/ezv268
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence of coronary artery bypass grafting off-pump versus on-pump: a systematic review with meta-analysis of over 16 900 patients investigated in randomized controlled trials

Abstract: In the present systematic review with meta-analysis, we sought to determine the current strength of evidence for or against off-pump and on-pump coronary artery bypass grafting (CABG) with regard to hard clinical end-points, graft patency and cost-effectiveness. We performed a meta-analysis of only randomized controlled trials (RCT) which reported at least one of the desired end-points including: (i) major adverse cardiac and cerebrovascular events (MACCE), (ii) all-cause mortality, (iii) myocardial infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 66 publications
8
88
1
3
Order By: Relevance
“…OPCAB, off-pump coronary artery bypass; ONCAB, on-pump coronary artery bypass; RCT, randomized controlled trial; CI, confidence interval; RR, relative risk. (1,3) found no difference in myocardial infraction rates between ONCAB or OPCAB. In the meta-analysis by Deppe et al (3), the incidence of low cardiac output and infection were reduced with use off-pump.…”
Section: Postoperative Renal Dysfunctionmentioning
confidence: 94%
See 3 more Smart Citations
“…OPCAB, off-pump coronary artery bypass; ONCAB, on-pump coronary artery bypass; RCT, randomized controlled trial; CI, confidence interval; RR, relative risk. (1,3) found no difference in myocardial infraction rates between ONCAB or OPCAB. In the meta-analysis by Deppe et al (3), the incidence of low cardiac output and infection were reduced with use off-pump.…”
Section: Postoperative Renal Dysfunctionmentioning
confidence: 94%
“…The majority of the large RCTs to date failed to show a difference in early mortality between off-pump and on-pump surgery (1,3,(9)(10)(11)(12)(13). One small sample size RCT by Fattouch et al showed a reduced mortality in patients with ST elevation undergoing urgent/emergent off-pump coronary surgery compared to on-pump surgery (14).…”
Section: Operative Mortalitymentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent meta‐analysis pooled angiographic data on 7011 grafts and found an OR of 1.51 for occlusion in the OPCAB arm (95% CI, 1.21–1.88; P =0.002) 84. Differences in surgeons’ experience, varying completeness of follow‐up, and angiographic definitions are the plausible reasons for the reported discrepancies.…”
Section: Opcab and Graft Patencymentioning
confidence: 99%